2014
DOI: 10.4172/2155-6105.s10-003
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Increases Needle Sharing among Cocaine users: Results from the COSMO Study

Abstract: Objective: Cocaine use and mental health disorders have both been separately identified as risk factors for blood borne virus infection. However, the contribution of specific underlying aspects of mental health to risks is not well documented. The aim of this study was to examine the association between psychological distress and risk behaviors for HIV and Hepatitis C infection among cocaine users.Methods: Individuals who either smoked or injected cocaine were recruited in community-based and addiction treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…These results are consistent with those in the quantitative study we conducted as part of the COSMO research project. In that study, analyses showed that severe psychological distress increased the odds of needle sharing but not of crack pipe sharing (Lévesque et al, 2014). However, participants' discourse suggested that in some cases, anxiety or desperation can influence sharing behaviours.…”
Section: Discussionmentioning
confidence: 85%
“…These results are consistent with those in the quantitative study we conducted as part of the COSMO research project. In that study, analyses showed that severe psychological distress increased the odds of needle sharing but not of crack pipe sharing (Lévesque et al, 2014). However, participants' discourse suggested that in some cases, anxiety or desperation can influence sharing behaviours.…”
Section: Discussionmentioning
confidence: 85%
“…The methodology used for the COSMO project was described in detail elsewhere . Briefly, to be eligible, participants must have used cocaine in the last month, either by smoking crack or by injection.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology was described in detail elsewhere (Lévesque et al, 2014). Briefly, to be eligible for the COSMO study, participants had to have used cocaine in the last month, either by smoking crack or by injection.…”
Section: The Cosmo Studymentioning
confidence: 99%